PERAN GURU SEBAGAI AGEN SOSIALISASI DALAM PEMBENTUKKAN KARAKTER DI SEKOLAH DASAR NEGERI CIBENING 03 KABUPATEN BOGOR - Ramadani, Fitri Alya; Nurlelah, Siti; Hasanah, Tita (Primer Edukasi Journal, 2026)
This study aims to determine the role of teachers as agents of socialization in instilling character values in students, particularly the values of honesty, responsibility, and mutual cooperation. The subjects in this study were class teachers, the principal, and representatives of fourth-grade students at SDN Cibening 03, Bogor Regency. This study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results of the study indicate that teachers play an important role not only in delivering lesson materials, but also as role models in shaping students' character through habituation, role models, and strengthening positive attitudes. Teachers consistently instill the values of honesty, responsibility, and mutual cooperation in daily learning activities and non-academic activities at school. The instillation of character values is carried out through direct practice, dynamic social interactions, and support from the entire school community. Thus, character education at SDN Cibening 03 runs in a structured, consistent manner, and shapes students into individuals with integrity and care for others.